New distribution record of Nigrohydnum nigrum Ryvarden (Polyporales: Basidiomycota) in the Atlantic forest - Robledo, Gerardo Lucio (2013)
Nigrohydnum nigrum Ryvarden is a rare polypore previously known only from two records in Brazil. During a herbarium revision at SP we have identified an old voucher specimen, extending the previously known geographic distribution to the Atlantic rain forest of Porto Alegre, Rio Grande do Sul State, Southern Brazil.